Hubungan Kepatuhan Minum Obat Anti Tuberkulosis Dengan Keberhasilan Pengobatan Tuberkulosis Pada Pasien Sensitif Obat Di Puskesmas Pamolokan Kabupaten Sumenep - Hamlatul Jamiliyatil Istiqomah; Rizdyana Firmaniar; Zetiawan Trisno; Aldita Cahyani Puspitasari (Jurnal Farmasi & Sains Indonesia, 2025)
Tuberculosis (TB) is a contagious infectious disease caused by the bacterium Mycobacterium Tuberculosis. Tuberculosis is transmitted through sputum or saliva containing tuberculosis bacilli. Tuberculosis is one of the world's health threats. The purpose of this study was to determine the relationship between adherence to taking anti-tuberculosis drugs and the success of tuberculosis treatment in drug-sensitive patients at the Pamolokan Health Center, Sumenep Regency. This study used a quantitative method with an observational survey approach using a Cross Sectional Research design. The population in this study were all drug sensitive tuberculosis patients undergoing treatment at the Pamolokan Health Center, Sumenep Regency in the January-June period, namely 32 people with total sampling techniques. The results of this study were 30 people as much as (93.75%) had compliant treatment compliance results. Based on the results of the study, it can be concluded that there is a relationship between adherence to taking medication with the success of anti-tuberculosis treatment. It is recommended that family members pay attention to sick family members, provide motivation, care, bring medical treatment and provide support to sick family members.